THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM) TOWARDS CONSUMERS’ PURCHASE DECISION AT BAKSO BOEDJANGAN, BANDUNG - Apriani, Dwi; Pradana, Mahir (IJRDO - Journal of Business Management, 2017)
The growth of Internet users in Indonesia is increasing every year, which is in line with the existing of social media’s popularity. Bakso Boedjangan catches an opportunity to excecute its promotion in which are both communication and interaction bounded called word of mouth, and interaction on social media called electronic word of mouth. The objective of this study of this study is to see how much the electronic word of mouth gives impact on purchasing decisions at Bakso Boedjangan Bandung. This research is quantitative descriptive data and causal analysis, respondents surveyed in this study amounted to 100 people who have made a purchasing decision in Bakso Boedjagan by using probability technique sampling. then carried out analysis to the data obtained by using simple linear analysis. The result showed that electronic word of mouth in the position of 69,1% with a number of high category, purchasing decision in the position of 73,6% with a number of high category. Based on the overall result of hypothesis testing, electronic word of mouth is partially significant effect on purchasing decisions at Bakso Boedjangan Bandung. This is evidence by tcount > ttable, which is 7,480 > 1.984. Based on the coefficient of determination, it shows that purchasing decision will be explained by the electronic word of mouth 36,36%, while the remaining 63,64% are influenced by other variables which are not examined in this study.